Asignación de recursos públicos por categoría de rubro y su relación con el gasto público en la Municipalidad Distrital de Belén, periodo 2019 – 2023 - Mori Pereyra, Jose Daniel (2024)
Municipalities, as public sector entities at the local government level, have the duty and responsibility to ensure the well-being and development of the population in their jurisdiction, and to do so, the allocation of public resources is essential so that they are used to finance public spending on all activities scheduled for a fiscal year that are to be executed. The research is titled "Allocation of public resources by category of item and its relationship with public spending in the District Municipality of Belén, period 2019 - 2023", its main objective being to determine the relationship between the study variables in an evaluated period of five (5) years; To meet the objectives of the research, techniques and instruments were applied that allowed for adequate analysis and interpretation of the information collected; The methodology was governed by a quantitative approach, descriptive level - correlational and non-experimental - longitudinal design. As the main result, we point out an intense positive relationship, according to the value obtained through Spearman's Rho correlation coefficient of 0.753.